Oxidative CO Cross‐Coupling of 1, 3‐Dicarbonyl Compounds and Their Heteroanalogues with N‐Substituted Hydroxamic Acids and N‐Hydroxyimides. Issue 11 (12th August 2013) - Terent'ev, Alexander O.; Krylov, Igor B.; Timofeev, Vladimir P.; Starikova, Zoya A.; Merkulova, Valentina M.; Ilovaisky, Alexey I.; Nikishin, Gennady I.
Abstract The oxidative CO cross‐coupling of 1, 3‐dicarbonyl compounds and their heteroanalogues, 2‐substituted malononitriles and cyanoacetic esters, with N‐substituted hydroxamic acids and N‐hydroxyimides was realized. The best results were obtained with the use of manganese(III) acetate [Mn(OAc)3] or the cobalt(II) acetate catalyst [Co(OAc)2cat.]/potassium permanganate [KMnO4] system as the oxidant. The synthesis can be scaled up to gram quantities of coupling products; yields are 30–94%. The reaction proceeds via a radical mechanism through the formation of nitroxyl radicals from N‐substituted hydroxamic acids and N‐hydroxyimides. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>